3(2t-5)+4t=

Simple and best practice solution for 3(2t-5)+4t= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2t-5)+4t= equation:


Simplifying
3(2t + -5) + 4t = 0

Reorder the terms:
3(-5 + 2t) + 4t = 0
(-5 * 3 + 2t * 3) + 4t = 0
(-15 + 6t) + 4t = 0

Combine like terms: 6t + 4t = 10t
-15 + 10t = 0

Solving
-15 + 10t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '15' to each side of the equation.
-15 + 15 + 10t = 0 + 15

Combine like terms: -15 + 15 = 0
0 + 10t = 0 + 15
10t = 0 + 15

Combine like terms: 0 + 15 = 15
10t = 15

Divide each side by '10'.
t = 1.5

Simplifying
t = 1.5

See similar equations:

| -7/14=c | | 165=30n+5 | | (33b-5)-8(4b+4)=-2 | | -88=11s-99 | | .5x^2+2x+3=x+7 | | -2.4/1.2=c | | 8.95+1.50n=26.95 | | 99=11x+y | | 41=-7x+2(-4x-32) | | -54=-9a-27 | | p=g+5u | | 8(2a-3)=-104 | | 8p+8q= | | .5x^2+2x=3x+7 | | a/6x=5x | | 24/14=m/35 | | 41=-7x+2(-4-32) | | -0.2x(x-6)+x=0.3(4-x) | | -5n+6n+15n-3n=3 | | 50+10t=30 | | -3x(2x+9)=0 | | 4m/3-m/6=-3 | | -45=63+9n | | 99-4x=14x+15 | | F(x)=4(6) | | 7-10x=157-45x | | 6t-54=36 | | r/3+7-r/5=3 | | 5/6(6x-3) | | -12m-24= | | 0.75+2x-1=3x-0.4 | | 7x-6(-x+20)=-224 |

Equations solver categories